The history of water salinity in the Pearl River estuary, China, during the Late Quaternary - Lloyd, Jeremy M. (2012)
This research reconstructed the Late Quaternary salinity history of the Pearl River estuary, China, from diatom records of four sedimentary cores. The reconstruction was produced through the application of a diatom–salinity transfer function developed based on 77 modern surface sediment samples collected across the estuary from shallow marine environment to deltaic distributaries. The statistical analysis indicates that the majority of sediment samples from the cores has good modern analogues, thus the reconstructions are reliable. The reconstructed salinity history shows the older estuarine sequence formed during the last interglacial was deposited under similar salinity conditions to the younger estuarine sequence, which was formed during the present interglacial. Further analysis into the younger estuarine sequence reveals the interplays between sea level, monsoon-driven freshwater discharge, and deltaic shoreline movement, key factors that have influenced water salinity in the estuary. In particular, a core from the delta plain shows the effects of sea-level change and deltaic progradation, while cores from the mouth region of the estuary reveal changes of monsoon-driven freshwater discharge. This study demonstrates the advantages of quantitative salinity reconstructions to improve the quality of reconstruction and allow direct comparison with other quantitative records and the instrumentally observed values of salinity.